Safeguarding the stranger : an Abrahamic theology and ethic of protective hospitality - Reaves, Jayme (Eugene, Oregon : Pickwick Publications, 2016)
What are the resources and teachings in Judaism, Christianity, and Islam that take hospitality--and its call to provide protective hospitality--seriously enough to inform shared action and belief on behalf of the threatened other? This book argues that protective hospitality and its faith-based foundations as seen in the Abrahamic traditions of Judaism, Christianity, and Islam merit greater theological attention and that the practice of protective hospitality in Christianity can be enhanced by better understandings of Judaism's and Islam's practices of hospitality, namely their codes and etiquettes related to honor. Safeguarding the Stranger draws especially on two currents in contemporary Christian theologies: (1) a contextual and political theological approach informed by liberation and feminist theologies, and (2) a cooperative and complementary theological approach informed by interreligious, Abrahamic, and hospitable approaches to dialogue. This book is unique in that it seeks to contribute to academic debates within theology and religious dialogue as well as to discussions within the fields of peace studies and conflict resolution on the positive role that religions might play in contexts of conflict.
Part 1. Hospitality, ethics, and theology. Locating the theological approach -- Extending hospitality : hospitality as ethical practice -- Hospitality and the Abrahamic traditions -- Part 2. Protective hospitality. Hospitality and protection -- Protective hospitality as a religious practice.
Keywords: Hospitality -- Religious aspects -- Christianity; Abrahamic religions; RELIGION -- Christian Theology -- Ethics; Abrahamic religions; Hospitality -- Religious aspects -- Christianity; Electronic books